Unsteady heat transfer by natural convection in the cavity of a passive heating room - Kurtbas, Irfan; Durmus, Aydin (Elsevier France-Editions Scientifiques Medicales Elsevier, 2008)
In this study, three dimensional unsteady state equations of heat transfer and flow have been solved numerically for a passive heating room using values of hourly averaged radiation during winter in Elazig region in Turkey. For this purpose, a room having volume of 44.8 m(3) (4 x 4 x 2.8 m) was considered. Variable heat flux boundary condition depending on time was applied on absorber surface using values of hourly averaged radiation. Convection boundary condition was used on glass surface, the walls and ceiling of the room by using overall heat transfer coefficient. Constant surface temperature (6 degrees C) was used for floor of the room. Experiments were carried out manufacturing a model room having the size of 1 x 1.2 x 1.2 in dimensions in order to maintain the corroboration of numerical solution. Governing equations for the model room built were solved numerically and compared to experimental data. It was seen that the model predictions agreed quite well with experimental data. The effect of overall heat transfer coefficient of glass on Nusselt number was also investigated. It was revealed that the overall heat transfer coefficient for low Rayleigh number affected the average Nusselt number more than that of high Rayleigh number. (c) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: passive heating; solar energy; numerical solution; variable heat flux